Impact of maternal body mass index on pregnancy outcomes following frozen embryo transfer: A systematic review and meta-analysis - Chucheng Tang; Fengming Tu (PLoS ONE, 2025)
Objective There is still a significant gap in understanding how maternal body mass index (BMI) impacts outcomes of pregnancy after frozen embryo transfer (FET). This review aims to evaluate the effects of various BMI categories on clinical pregnancy and live birth rates in women undergoing FET. Methods PubMed, Scopus, Embase, and Web of Science databases were searched for studies, published up to March, 2024, using the keywords “obesity”, “overweight”, “obese”, “maternal body mass index,” “pregnancy outcomes,” “frozen embryo transfer,”. Eligible studies were selected based on predefined inclusion criteria, statistical analysis was performed using a random-effects model, and ther results were presented as odds ratios (OR) with 95% confidence intervals (CI). Results A total of 17 studies were included in the meta-analysis. Pooled findings indicate significantly reduced live birth rate in underweight (OR 0.93; 95% CI: 0.89, 0.98) and obese (OR 0.85; 95% CI: 0.77, 0.93) women but not in those who were overweight (OR 0.96; 95% CI: 0.92, 1.00), compared to those with normal BMI. Further, only those women who were underweight (OR 0.91; 95% CI: 0.85, 0.97) had reduced odds of clinical pregnancy rate but not those who were overweight (OR 0.99; 95% CI: 0.94, 1.05) or obese (OR 0.92; 95% CI: 0.82, 1.03). Conclusion Maternal BMI impacts pregnancy outcomes after frozen embryo transfer, with underweight and obese women having lower live birth rates and only underweight women showing reduced clinical pregnancy rates compared to those with normal BMI. These findings underscore the importance of addressing BMI in women undergoing FET to improve pregnancy outcomes.